Epistemological constructs of video games as venues of learning interactions of the self, the characters, and the environment - Lesaca, John Paul O.; Muega, Michael Arthus G.; Muega, Maricris B. Acido; Que, Elenita N. (Quezon City College of Education, University of the Philippines Diliman, 2024)
This study explores the realm of video gaming and its impact on players’ learning and personal development, focusing specifically on the popular game Genshin Impact. Through a grounded theory methodology, the research aimed to uncover the memorable aspects of the game, the holistic learning experiences it fosters, the feature of cooperative play, players’ perceptions of parental involvement, and the values gained through gaming. The objective was to understand how Genshin Impact contributes to the formation of epistemological constructs in learning and to determine how players can obtain knowledge through this versatile platform. It is when players utilize its immersive environment and interactive gameplay, the game facilitates skill and knowledge acquisition and behavioral changes among its players. Among the fourteen (14) players interviewed for the study, the findings highlight the game’s role in promoting player engagement, skill development, collaborative experiences, and value and knowledge acquisition, shedding light on its potential as an educational tool in contemporary learning environments. This study emphasizes the importance of providing a safe space for self-expression within the game and underscores the need for parental and educational guidance to maximize the positive impacts of gaming. The emergent theory of “Crafting meaningful experiences and reflections to foster personal growth and development” captures the transformative potential of video games as a learning venue. These insights contribute to a deeper understanding of how video games like Genshin Impact can be integrated into educational practices to foster personal growth and development of its players.
Thesis
Includes bibliographical references (118-125 leaves)
Keywords: Video games in education -- Philippines; Mobile games; Video games -- Philosophy; Educational games; Knowledge, Theory of